Characterization of the honey bee and stingless bee gut microbiota: A hidden diversity and host-specific microbiomes from sub-Saharan-African region - Slippers, Bernard (University of Pretoria, 2021)
Thesis (PhD (Molecular Biology and Biotechnology))--University of Pretoria, 2020.